The Utilization of Heat Exchangers for Energy Conservation in Air Conditioning - Yau, Y. H.; Wong, S. W.; Tong, C. Y.; Than, C. F. (Universiti Putra Malaysia Press, 2001)
This paper investigates the characteristics of heat exchanger (HPHE) as an efficient coolness recovery unit in air conditioning through experimental studies. It was conducted under a multiple-nozzle code tester based on the ASHRAE standards. The wind tunnel was subjected to airflow with considerable variation in its inlet air temperature. Among the factors being investigated are the air velocity, inlet and outlet air temperatures, overall efficiency and the number of rows in longitudinal direction. The data obtained were compared with the results predicted by previous theoretical studies. Good agreement was observed.